PENGARUH JIWA KEWIRAUSAHAAN KEPALA MADRASAH TERHADAP JIWA KEWIRAUSAHAAN SISWA MA SE - KECAMATAN SOREANG: - - Hoerudin, Heri; Nasrudin, Endin; Nugraha, Mulyawan Shafwandi; Sahroni, Dadang; Widaningsih, Sri; Hilman, Cecep (Komunitas Manajemen Kompetitif, 2023)
The madrasah head is the top leader in an educational institution, and should have one of the competencies, namely entrepreneurial competence which has an impact on improving the quality of education. The purpose of this study was to determine the influence of the madrasa head's entrepreneurial spirit on the entrepreneurial spirit of students. This study uses a quantitative approach in causal correlation techniques while the method of data fulfillment is through questionnaires, observations, interviews, and documentation studies. Researchers only see and know the relationship between one variable and other variables based on causal relationships or research constellations. The results of this study are based on the results of statistical calculations showing that the probability value is greater than sign 0.05, which means that the entrepreneurial spirit of the madrasah head does not have a significant effect on the entrepreneurial spirit of students, one of the reasons is that there are no operational implementation guidelines on the entrepreneurial competence of madrasah heads. Recommendations from researchers for madrasah heads to make operational guidelines for the implementation of entrepreneurial competencies that rely on regulations that apply in a structured and comprehensive manner, starting from managing entrepreneurial values or spirit as the foundation of entrepreneurship to practical entrepreneurship in an effort to improve the quality of madrasas.